Expression of Myosin 5a splice variants in murine stomach. Issue 10 (3rd May 2021) - Carew, Josephine A.; Cristofaro, Vivian; Siegelman, Nicolas A.; Goyal, Raj K.; Sullivan, Maryrose P.
Abstract: Background: The motor protein, Myosin 5a (Myo5a) is known to play a role in inhibitory neurotransmission in gastric fundus. However, there is no information regarding the relative expression of total Myo5a, or of its alternative exon splice variants, across the stomach. This study investigated the differential distribution of Myo5a variants expressed within distinct anatomical regions of murine stomach. Methods: The distribution of Myo5a protein and mRNA in the stomach was assessed by immunofluorescence microscopy and fluorescent in situ hybridization. Quantitative PCR, restriction enzyme analysis, and electrophoresis were used to identify Myo5a splice variants and quantify their expression levels in the fundus, body, antrum, and pylorus. Key Results: Myo5a protein colocalized with βIII‐Tubulin in the myenteric plexus, and with synaptophysin in nerve fibers. Total Myo5a mRNA expression was lower in pylorus than in antrum, body, or fundus ( p  < 0.001), which expressed equivalent amounts of Myo5a. However, Myo5a splice variants were differentially expressed across the stomach. While the ABCE splice variant predominated in the antrum and body regions, the ACEF/ACDEF variants were enriched in fundus and pylorus. Conclusions and Inferences: Myo5a splice variants varied in their relative expression across anatomically distinguishable stomach regions and might mediate distinct physiological functions in gastric neurotransmission. Abstract : This study evaluated expression across the murine stomach of the processive actin‐based motor protein, Myosin 5a (Myo5a), which participates in the short‐range transport of cytoplasmic cargos, including synaptic vesicles. The results indicated that Myo5a protein is localized to the cell bodies and processes of enteric nerves, and that mRNA corresponding to Myo5a splice variants associated with brain versus skin were, respectively, expressed more highly in the antrum and body, versus the fundus and pylorus. Differences in Myo5a splice variant expression may underlie distinct functional roles for this motor protein within these stomach regions.